Current technologies for nutrient recovery in aquaponic systems: a review - Nishanth, Drishya; Somanathan Nair, Chythra; Manoharan, Ramya; Subramanian, Radhakrishnan; Salim, Irfan; Maqsood, Sajid; Jaleel, Abdul (Frontiers in Sustainable Food Systems, 2025)
Aquaponic systems are integrated food production systems that recycle nutrients through the combination of aquaculture and hydroponics. Nutrient recovery in aquaponic systems faces major challenges such as imbalances in nutrients, inefficiencies in nutrient extraction, and scalability constraints. Various methods have been investigated to address these challenges, including physical approaches (e.g., filtration and sedimentation), chemical strategies (e.g., struvite precipitation), and biological techniques (e.g., microbial digestion and nutrient mineralization). Additionally, hybrid strategies that are a combination of these methods are also reviewed for their potential to improve nutrient recovery and system performance in aquaponic systems. Emerging technologies such as hybrid biofilters and phototrophic bioconversion show promise in addressing these challenges, though they require further research for full-scale implementation. This review comprehensively examines the sources and composition of aquaponic sludge, the role of macro- and micronutrients, and critically analyses various physical, chemical, and biological nutrient recovery strategies. It also highlights innovative approaches and their integration potential. By synthesizing the strengths and limitations of these methods, this review provides a roadmap for optimizing nutrient recovery to advance low-waste, circular aquaponic models.